Rice Yellow Stunt Nucleorhabdovirus Matrix Protein Mediates Viral Axonal Transport in the Central Nervous System of Its Insect Vector - Wang, Haitao; Wang, Juan; Zhang, Qian; Zeng, Tianbao; Zheng, Yuemin; Chen, Hongyan; Zhang, Xiao-Feng; Wei, Taiyun (Frontiers in Microbiology, 2019)
Persistently transmitted plant viruses encounter multiple membrane and tissue barriers in the process of completing their infection routes within their insect vectors. Some of these viruses have been reported to overcome the elaborate barriers of the central nervous system (CNS) to travel through the nervous tissues, but the specific mechanisms of this process remain unknown. Here, we report the axonal transport mechanism of rice yellow stunt virus (RYSV), a nucleorhabdovirus, in the CNS of the green rice leafhopper (Nephotettix cincticeps). The infection route of RYSV in the internal organs of its insect vector after ingestion of the virus was investigated by immunofluorescence microscopy. RYSV was first detected in the epithelial cells of midgut regions, from where it proceeded to the nervous system, and finally into the salivary glands. We then utilized immunofluorescence and electron microscopy to investigate the distribution of RYSV particles within the leafhopper CNS, demonstrating that non-enveloped viral particles distributed along the microtubule-based neurofilaments in the axon cytoplasm following the direct interaction of leafhopper α-tubulin with the RYSV M protein. Tubulin inhibitors inhibited the dissemination of RYSV to the CNS, then into the salivary glands in leafhoppers. We therefore describe a mechanism of plant virus transport through CNS axons as an alternative means of rapid viral dissemination in an insect vector.